2007
DOI: 10.1016/j.jneuroim.2007.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine changes during interferon-beta therapy in multiple sclerosis: Correlations with interferon dose and MRI response

Abstract: We investigated serum (IL-10 and IL-12p70) and cellular cytokine levels (IL-10, IL-12p40, IL-12p70, IFN-γ) in stimulated PBMC over 24 weeks in 15 Relapsing Remitting Multiple Sclerosis (MS) patients randomized to receive once-weekly (qw) IFN-β-1a 30 ug intramuscularly (IM) (n=8) or three-times-weekly (tiw) IFN-β-1a 44 ug subcutaneously (SC) (n=7). Overall, IFN-β treatment increased cellular IL-10 (p<0.01) levels and the ratios of cellular IL-10/IL-12p40 (p<0.01) and IL-10/ IL-12p70 (p<0.02) while cellular IFN-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(27 citation statements)
references
References 45 publications
1
24
0
2
Order By: Relevance
“…More notably, consistent with an inhibitory role of Sema4A in IL-10 production (35), we found that patients with high serum Sema4A levels had low serum IL-10 levels. Because IL-10 has been linked to the beneficial effects of IFN-b treatment (24,48), it is plausible that high Sema4A levels result in decreased IL-10 levels, leading to the unresponsiveness to IFN-b therapy.…”
Section: Discussionmentioning
confidence: 99%
“…More notably, consistent with an inhibitory role of Sema4A in IL-10 production (35), we found that patients with high serum Sema4A levels had low serum IL-10 levels. Because IL-10 has been linked to the beneficial effects of IFN-b treatment (24,48), it is plausible that high Sema4A levels result in decreased IL-10 levels, leading to the unresponsiveness to IFN-b therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Since IFNβ comprises a first-line defense against acute virus infections, the antiviral effects of various therapeutic IFNβ variants may represent a partial explanation for their favorable effects in MS. Another rationale for clinical trials with IFNβs is based on the assumption that cytokines from both immune and non-immune cells play a major role in MS pathophysiology and that IFNβ downregulates proinflammatory Th1 cytokines and upregulates antiinflammatory Th2 cytokines [36,37,38]. However, changes in the profile of Th1/Th2 cytokines during long-term monotherapy with IFNβ-1a or IFNβ-1b have not been investigated in patients with RRMS.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, many serum biomarkers are non-specific indicators of systemic inflammation and may also be altered during even minor infections [4]. Another obstacle to interpreting studies of biomarkers in response to therapy is differences in the formulations of IFN-β used in different studies, which have been shown to have different effects on biomarkers of disease [5][6][7]. Numerous biomarkers of disease activity have been explored encompassing cytokines, chemokines, immune cell subsets, costimulatory molecules, antibodies, vascular adhesion and permeability and neuronal and glial damage, among others (Tables 3-8).…”
Section: Introductionmentioning
confidence: 99%